Peningkatan aktivitas fagositosis dan produksi nitrit oksida pada makrofag peritoneum tikus Sprague Dawley yang diberi Lactobacillus plantarum Mut7 dan ekstrak serat ubi jalar - Lily Arsanti Lestari; Marsetyawan Heparis Nur Ekandaru Soesatyo; Susi Iravati; Eni Harmayani (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2012)
Background: Macrophages play an important role as part of the innate immune response in the gut and they represent one of the first lines of nonspecific defense against bacterial invasion. Previous studies indicated that probiotics and prebiotics may act as an immunomodulator agents. Nevertheless, research on the immunomodulatory effect of local materials has never been performed.Objective: To study the effects of Lactobacillus plantarum Mut7 and sweet potato fiber on the activity and Nitric Oxide (NO) production of peritoneal macrophages of Sprague Dawley rats.Method: Ninety six Sprague Dawley rats aged 8 weeks were divided into two groups; A (not infected with Salmonella typhimurium) and B (infected with S. typhimurium). Each group was divided into 4 subgroups and assigned to standard AIN-93M diet (KON), 109 CFU/ml of L. plantarum Mut7 (PRO), modified AIN-93M diet with sweet potato fiber (PRE), and both component (SIN). After 3 weeks of treatment, 6 rats of each subgroup were sacrificed and the peritoneal macrophages were isolated and analysed for its activity and NO production. The rest of the rats continued the treatments for another 2 weeks. At the end of the experiment, they were sacrificed and the peritoneal macrophage were isolated and analysed for its activity and NO production.Results: Oral administration of L. plantarum Mut7, sweet potato fiber, or both improve phagocytic activity of peritoneal macrophage which was indicated by an increase in the percentage of macrophages that phagocyte latex particles (p<0.05) and an increase in the number of latex particles engulfed by macrophages either after 3 or 5 weeks of treatment (p<0.05). Oral administration of L. plantarum Mut7, sweet potato fiber, or both were unable to increase the nitric oxide production after 3 weeks of treatment (p>0.05), but after 5 weeks of treatment the production of NO was significantly increased (p<0.05).Conclusion: L. plantarum Mut7, sweet potato fiber, or both increase the non specific immune response as they could improve the activity and NO production of peritoneal macrophages.